O olhar que revela o desenvolvimento emocional de um bebê abrigado - NASCIMENTO, Rose Daise Melo do (Universidade Federal do Pará, 2014)
This study is a qualitative research that aimed to observe and analyze on the psychoanalytic approach, the emotional development of an institutionalized infant. For this there was a case study, which consisted in adapting the methodological tool of the Bick method of Infant Observation. The adaptations relate to the environment that is institutional, reduction of observation time for four months, the context of disclosures that due to shortage of researchers who use this method in Belém, most supervision were restricted to the pair observer and supervisor, and the latter served as advisor for this parallel study. We conducted the research in a state housing that welcomes children from birth to six years, where Miguel lived, a baby who was abandoned due to financial difficulties justified by the mother. Miguel has been observed since their 20 days of life until four months, through weekly observations lasting one hour, totaling 20 observations, which were recorded and subjected to supervision. The results were organized into three main chapters: 1) On the emotional development of babies going back to the theoretical field of child psychoanalysis 2) I am seen, therefore I am outlining the relationship between infant-observer, with a focus on transference and countertransference issues that permeated the ratio 3) Good care, bad care which addresses the care environment experienced by Miguel in the context of residential care and 4) The affective coloring of Miguel covering the important aspects of emotional development of Miguel at the institution. At the end of this journey, Miguel has proven to be a baby during the first month experienced catastrophic anxieties, which required care and restraint, used the cry and look to attract contact, however, was rarely served by various reasons inherent in the context of institutionalization; subsequently proved to be more familiar with the environment, using resources such as smiles and vocalizations to relate. Despite the instability and inconsistency of care, Miguel was interpreted as a symbol of the baby that overcoming obstacles and facing an ambivalent world in its fullest expression, revealed that there is no ideal situation for emotional development.